Implementation of PKH in Community Empowerment Efforts in Mulyoagung Village, Bojonegoro District, Bojonegoro Regency - Nabila Elvira Putri; Ertien Rining Nawangsari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Poverty remains a strategic issue in regional development, including in Bojonegoro Regency, despite showing a general downward trend. The Family Hope Program (PKH), as a social protection policy, is expected to improve the welfare of the poor, but its effectiveness at the village level still requires in-depth study. This study aims to analyze the implementation of PKH and its contribution to reducing poverty in Mulyoagung Village, Bojonegoro District. The method used is a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation of relevant informants. The results indicate that communication, resources, disposition, and bureaucratic structure in PKH implementation have been effective. However, several obstacles remain, including low knowledge about business development in economic empowerment. This study contributes in the form of an overview of PKH implementation at the village level and serves as evaluation material for village governments in improving program effectiveness.